Effectiveness of Vitamin C and Vitamin E Antioxidant Combination on Caspase-3 Expression in Wistar White Rat Pulmonum Contusion - Bermansyah; Gama Satria; Ahmad Umar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Introduction: Pulmonary contusions can cause a progressive inflammatory response. Activation of TNF-Î± cytokines and reactive oxygen species (ROS) can cause pulmonary cell death. Antioxidants can have the potential to neutralize ROS. The purpose of this study is to determine the effectiveness of antioxidant administration in maintaining pulmonary cell function in wistar rats that have been induced to experience pulmonary contusions through caspase-3 levels. Methods: This study was an in vivo experimental study conducted on thirty male wistar rats and divided into five groups (n = 6): control, pulmonary contusion + asthaxanthine 5 mg/kgBW, pulmonary contusion + vitamin C and E 50 mg/kgBW, pulmonary contusion + vitamin C and E 100 mg/kgBW, pulmonary contusion + vitamin C and E 200 mg/kgBW. The value of Caspase-3 is evaluated by the IHC. All data analyzes used SPSS 18. Results: Low doses of antioxidants have the potential to reduce pulmonary cell death in wistar rats induced by pulmonary contusions. Conclussion: Vitamin C and E effective to reduce polmonary cell death in pulmonary contusion.